Government with a Cast of Dozens: Policy Capacity Risks and Policy Work in the Northern Territory. Issue 2 (30th January 2015) - Carson, Dean; Wellstead, Adam
Abstract : There are a number challenges to maintaining high‐quality policy capacity in sparsely populated areas such as Australia's Northern Territory (e.g. natural resource dependent economy, prominence of Indigenous issues, provision of local services). Moreover, the Territory government has recently been undergoing a host of public sector changes. This paper utilises survey methodologies of policy workers that were recently developed in Canada and examines nine risk factors to policy work. A survey of 119 policy workers in the Northern Territory was conducted in 2013. The analysis examined four key policy‐work areas (policy activities, barriers, areas for improved policy capacity, nature of change in work environment). The survey findings offer some practical insights for managers. Formal policy‐work training is recognised as critical. Policy capacity may be increased through better inter‐departmental (and potentially inter‐governmental) cooperation and information sharing, more opportunities to engage with non‐governmental stakeholders, and more opportunities for those leaving the full‐time Northern Territory policy workforce to continue to contribute. From a conceptual point of view, the extent to which 'policy capacity' as commonly conceived in the literature is applicable to contexts, such as Australia's Northern Territory, warrants further examination. Abstract : A survey of 119 policy workers in the Northern Territory was conducted in 2013. The analysis examined four key policy work areas (policy activities, barriers, areas for improved policy capacity, nature of change in work environment). The survey findings offer some practical insights for managers.